Chromatic polynomials and chromaticity of graphs - Dong, F. M., 1962- (World Scientific Pub., 2005)
This is the first book to comprehensively cover chromatic polynomialsof graphs. It includes most of the known results and unsolved problemsin the area of chromatic polynomials. Dividing the book into threemain parts, the authors take readers from the rudiments of chromaticpolynomials to more complex topics: the chromatic equivalence classesof graphs and the zeros and inequalities of chromatic polynomials.